Kajian Mutu Mi Instan Yang Terbuat Dari Tepung Jagung Lokal Riau dan Pati Sagu - Maylani, Dony; Ali, Akhyar; Pato, Usman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this study was to obtain the best ratio of corn flour and sago starch on the quality of instant noodles. A completely randomized design with five treatments and flour replications was used. The treatment consist were JST1 (corn flour 60% : sago starch 30% : tapioca 10%), JST2 (corn flour 55% : sago starch 35% : tapioca 10%), JST3 (corn flour 50% : sago starch 40% : tapioca 10%), JST4 (corn flour 45% : sago starch 45% : tapioca 10%) and JST5 (corn flour 40% : sago starch 50% : tapioca 10%). The results show that the ratio of corn flour and sago starch were significantly affected the quality of instant noodles. The best treatment of this study was JST2 with, water content before frying of 10,73% (w/w), moisture content after frying of 6,39% (w/w), protein content of 7,42% (w/w), total acid number of 0,14% (w/w), the intackness of 95,36% (w/w), and rehydration time 10 of minutes 6 seconds.   Keywords: instant noodles, corn starch, sago starch